Procesos de construcción de la opinión pública, a través de los programas de opinión: contacto directo y perspectiva 7, de Ecuavisa y Ecuador tv, durante el período mayo - junio del 2014 - Suntasig Masabanda, Edgar Paúl (2015)
The research objective is to identify how is public opinion construction processes on the communication media, specifically on television, processes which are centered on topics selection for release content to public debate. With this study it will be known how TV channels: Ecuador TV a public entity, and Ecuavisa a private media, release topics coupled to their policies. Ideological orientation, and their own interest. The analysis has permitted to evidence that form and the intension of the content are different….